Urban Heat Island and Thermal Comfort Assessment in a Medium-Sized Mediterranean City - Georgios Kalogeropoulos; Argiro Dimoudi; Pavlos Toumboulidis; Stamatis Zoras (Atmosphere, 2022)
One of the greatest issues nowadays is that of the urban heat island effect on the thermal conditions inside cities. The air temperature inside the city core is warmer than that in suburbs, thus deteriorating the quality of life for citizens and making outdoor spaces uncomfortable in terms of thermal comfort. This phenomenon is usually assessed in large scale cities worldwide and less often in medium-sized towns. The current study aimed to investigate the urban heat island effect and, therefore, to assess the outdoor thermal comfort conditions in a medium-sized city. More specifically, the methodology of the current study includes: (i) the combination of different monitoring techniques to quantify the urban heat island effect in a medium-sized Mediterranean city. Both in situ measurements and remote sensing techniques were applied to assess the urban heat island effect in terms of both the canopy layer (CUHI) and the surface (SUHI); (ii) the identification of the parameters that affect thermal comfort and the identification of the most appropriate bioclimatic indices that determine outdoor thermal comfort in the city of interest. Both questionnaire survey and in situ measurements took place on a sidewalk in the city of Xanthi, Northern Greece, during the summer. The CUHI effect was obvious, especially in the morning and afternoon. Downscaled MODIS satellite images also showed that the intensity of SUHI was higher in the morning and afternoon. Apart from air temperature, important differences in the values of most microclimatic parameters were recorded between the meteorological station placed inside the urban area and those gathered from a nearby meteorological station. The narrow roads, the thermal properties of construction materials, and the absence of greenery characterized the area of interest and may be the key factors creating these differences in climate. Concerning the thermal comfort assessment, the most significant parameters were the air temperature and solar radiation, although, both empirical and direct indices were found to describe the comfort values well. According to the results, downscaling techniques are also important for the SUHI effect to be investigating in detail in medium-sized urban environments.